The Supersolvable Order of Hyperplanes of an Arrangement (Communications in Mathematical Research, 2021)
This paper mainly gives a sufficient and necessary condition for an orderof hyperplanes of a graphic arrangement being supersolvable. In addition, we givethe relations between the set of supersolvable orders of hyperplanes and the set ofquadratic orders of hyperplanes for a supersolvable arrangement.
Keywords: quadratic arrangement; graphic arrangement; supersolvable order of hyperplane; quadratic order of hyperplane; supersolvable order of vertices.